Inquiring into culture in our foreign-language classrooms - Castro, Damaris (Colombian Applied Linguistics Journal, 2007)
This article presents some theoretical reflections about the concept of culture and its paramount importance in foreign language classrooms, as a basis for examining curriculum as inquiry, a facilitative tool to incorporate culture in courses in the Bachelor’s degree in the Teaching of English as a Foreign Language at the National University of Costa Rica (UNA). Feasible solutions to common problems that teachers face when trying to incorporate culture in their classrooms, are also discussed.